Surface silanization and grafting reaction of nano-silver loaded zirconium phosphate and properties strengthen in 3D-printable dental base composites. (October 2020) - Liao, Wenbo; Zheng, Shaona; Chen, Shenggui; Zhao, Lili; Huang, Xiangxuan; Huang, Lele; Kang, Shimin
Abstract: In this work, surface modification of nano silver-loaded zirconium phosphate (6S-NP3) were obtained from simultaneous silanization of γ-methacryloxypropyltrimethoxysilane (MPS) and grafting reaction of methyl methacrylate (MMA), and then mixed with denture base resin (E-Denture) to prepare denture base composites using 3D printer printing. FT-IR spectra confirmed that surface silanization and grafting reaction had occurred and MPS and MMA were successfully anchored on the surface of 6S-NP3. XRD results demonstrated that surface modification had occurred on the surface of hexagonal lattice. The average diameter data indicated that the surface modification decreased the average diameter of nanoparticles. The water contact angle (WCA) was found increasing as the surface modification. SEM images illustrated that the dispersion and compatibility of nanoparticles in denture base composite materials had improved. The results of mechanical properties presented that composites with the addition of P-6S-NP3 nanoparticles achieved higher flexural strength, flexural modulus and impact strength. The data of antibacterial activities revealed that composites had exhibited good antibacterial activities against either S . aureus or E. coli and the latter showed better antibacterial efficacy than the former. Graphical abstract: Image 1 Highlights: Simultaneous surface silanization and grafting reaction on the surface of silver-loaded zirconium phosphate were occurred. Denture base composites were prepared by 3D printer printing. The dispersion and compatibility of nanoparticles in denture base composites had promoted by surface modification. Denture base composites exhibited better mechanical properties and antibacterial activities.